청소년의 비합리적 신념과 공격성의 관계에서 일차사고와 이차사고의 순차적 매개효과 - 신민진; Shin Min-jin; 하은혜; Ha Eun-hye (한국놀이치료학회지(놀이치료연구), 2020)
본 연구는 비합리적 신념이 공격성에 미치는 영향에서 우울인지, 사회불안인지, 적대적 인지, 신체적 위협인지의 일차사고와 타인비난, 최악 가정하기, 축소화의 이차사고가 순차적으로 매개하는 지를 검증하였다. 중학생 649명을 대상으로 일반적 태도 및 신념 척도(GABS-K), 아동용 자동적 사고 척도(K-CATS), 자기위주 인지왜곡 척도(K-HIT), 또래 갈등 척도(PCS)를 사용하여 자기보고평가를 실시하였다. 그 결과 첫째, 청소년의 비합리적 신념이 공격성에 미치는 영향에서 일차사고와 이차사고의 순차적 매개효과를 확인한 결과, 비합리적 신념은 일차사고와 이차사고에 정적으로 영향력이 유의하였고, 공격성에서는 영향력이 유의하지 않았다. 둘째, 간접 효과의 유의성을 확인한 결과, 비합리적 신념과 공격성 사이에 이차사고가 부분매개효과를 보였고, 비합리적 신념과 공격성 사이에 일차사고와 이차사고가 순차적으로 매개하였다. 반면, 비합리적 신념과 공격성 사이에 일차사고의 매개효과는 통계적으로 유의하지 않았다. 이를 통해 초기 상황에 대한 지각과 평가해석을 하는 일차사고의 특성과 일차사고를 통해 위협으로부터 자신을 지키기 위한 대처행동을 고려하는 이차사고의 특성을 확인하였다. 본 연구는 청소년의 부정적 인지가 공격성에 이르는 경로를 확인하였다는데 의의가 있다. The purpose of this study was to verify the sequentially mediating effects of the primary thoughts and secondary thoughts of Adolescents. The subjects comprised 649 middle school students in grades 1 through 3 in Seoul, Gyeonggi and, Incheon. They were assessed by means of the General Attitude and Belief Scale (GABS-K), the Children's Automatic Thought Scale (K-CATS), How I Think (K-HIT), and the Peer Conflict Scale (PCS). As a result of confirming the sequential mediating effect of primary and secondary thought and how they interact with the effects of the irrational beliefs of adolescents in terms of aggression, it was found that irrational beliefs had a significant influence on primary and secondary accidents, but not on aggression. As a result of confirming the significance of these indirect effects, secondary thought showed a partial mediating effect between irrational beliefs and aggression, and primary and secondary thoughts were sequentially mediated between irrational beliefs and aggression. On the other hand, the primary thought between irrational beliefs and aggression was not found to be significant. Lastly, this study has identified the characteristics of primary thoughts as they are used to perceive and evaluated an initial situation, and the characteristics of secondary thought that considered coping behaviors used by the subjects to protect themselves from threats through primary thought.